Rates of Switching First-Line Antiretroviral Regimen Tenofovir-Emtricitabine-Efavirenz combination in a Primary Care Service in South Africa - Huang, David (Department of Public Health and Family Medicine, 2020)
Introduction: Tenofovir-Emtricitabine-Efavirenz (TEE) fixed-dose-combination (FDC) has been recommended since 2013 as the first-line antiretroviral therapy (ART) for treating HIV for people living with the virus (PLWH) in South Africa. More evidence has emerged to show long term adverse effects of Efavirenz(EFV). This study assesses the adverse effect profile of TEE by determining the event rate of switching from co-formulation and the reason for such switch. Method: This retrospective cohort study involved the review of the records of HIV infected adults receiving the TEE fixed dose combination ART over a 5-year period. All adult patients 18 years age or above, non-pregnant, previous ART treatment naïve that started TEE during 1 September 2014 and 31 August 2019 were included. Follow-up was censored at first drug change, transfer-out, loss-of-follow-upon deaths. Results: Two-thousand-and-ninety subjects were newly initiated on ART and 1961 met the inclusion criteria. Ninety-four patients (4.8%) had drug-changes prior censor date whereas 1867 remained on TEE. Forty-seven (50%) were single drug changes due to adverse effects and the other 50% were regimen changes as result of virological failure. The median time to change for TDF and EFV were 0,24 and 1,26 person years respectively. The median time to change for virological failure was 1,02 years. Patients with baseline CD4 count less than 200 cells/uL has higher risk of switch event. The proportion of poor outcome (death or loss to follow up) in patients with no drug switches (8,78%) was similar to those of patients with drug changes(8,5%). Conclusion: Tenofovir-Emtricitabine-Efavirenz combination treatment remains an excellent first-line ART option for people living with HIV, with a low rate of substitutions due to toxicity and high virological suppression. With the advent of Tenofovir-Lamivudine-Dolutegravir combination regimen as the preferred first-line, clinicians should remain cognisant of Tenofovir adverse drug effects.